Pengaruh Konseling Teman Sebaya Melalui Pendekatan Client Centered Terhadap Resiliensi Remaja Korban Bullying Pada Siswa Kelas VIII di SMP IT Nurul Fadhilah Tahun Ajaran 2025/2026 - Cinta Wulandhara Lubis; Nani Barorah Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of peer counseling using a client-centered approach on the resilience of adolescent bullying victims among 8th-grade students at SMP IT Nurul Fadhilah during the 2025/2026 academic year. A quantitative method was employed. The study utilized a quasi-experimental design, specifically a one-group pre-test/post-test design. The subjects consisted of six 8th-grade students at SMP IT Nurul Fadhilah (Academic Year 2025/2026) who exhibited low resilience scores as bullying victims; these subjects were selected using purposive sampling. Data collection involved a questionnaire containing statements designed to assess the level of resilience behavior among these adolescent bullying victims. The data were subsequently analyzed using the Wilcoxon test to determine if there was an effect on the students' resilience. Results showed a mean pre-test score of 110.833 and a mean post-test score of 133.500 for the experimental group. The Wilcoxon signed-rank test yielded a calculated J-value (J-count) of 6 and a critical J-value (J-table) of 0 (for n=6, α=0.05). Based on the hypothesis acceptance and rejection criteria where the hypothesis is accepted if J-count > J-table the result (6 > 0) indicates a significant effect of the treatment on the experimental group; thus, peer counseling using a client-centered approach demonstrated a significant influence on resilience. This indicates that the influence of peer counseling services using a client-centered approach on the resilience of adolescent bullying victims among 8th-grade students at SMP IT Nurul Fadhilah (Academic Year 2025/2026) is supported.